Live streaming influences consumer’s purchase intention in social commerce - Muhammad Firdaus Helmi Shafee; Nur Ilyana Syafiqah Zulkifli; Nurulezzah Zolkafli; Tan Eng Ping (2023)
People nowadays utilise social media to communicate and browse the internet in their leisure time. Furthermore, individuals are utilising social media as a kind of entertainment in their spare time. As information technology has advanced, live streaming commerce has emerged as a new sort of e-commerce activity. Although live-stream shopping is becoming increasingly popular in Malaysia, little study has been undertaken to explore the elements that motivate customers to purchase via live-stream. This research looks at how live broadcasting affects purchase intention (PI) in social commerce. Based on the S-O-R framework, this study's response included price promotion, promotion time limit, visual appeal, and consumer-streamer interaction. In this study, the target respondents are West Malaysian internet users who have seen a live-stream video about a product or service on social media. The data collected will be analyzed using the SPSS version to verify the statistical data analysis. These findings also showed that managers of live streaming e-commerce should improve price promotion, promotion time limit, visual appeal, and consumer-streamer interaction to increase consumers' reported delight.